Five new species of the genus Nannopus (Copepoda: Harpacticoida: Nannopodidae) from intertidal mudflats of the Korean West Coast (Yellow Sea) - Vakati, Vinod; Lee, Wonchoel (Zootaxa, 2017)
Five Nannopus Brady, 1880 species that are new to science are described from the intertidal mudflats of the Korean West Coast, Yellow Sea (South Korea). Nannopus minutus sp. nov. and N. dimorphicus sp. nov. belong to a group of species defined by seven elements on P4 exp-3, and these two species are unique by the pinnate caudal seta III. These species differ in the number of dorsal integumental windows on the cephalothorax (three in N. minutus, one in N. dimorphicus), shape of the distal small seta on the P4 endopod (naked in N. minutus, pinnate in N. dimorphicus), shape of the caudal seta IV (inflated and leaf-shaped in N. minutus, with a globular expansion at its insertion and slender in N. dimorphicus), and shape of the caudal seta V (anterior part cylindrical in N. minutus, inflated and bulbous in N. dimorphicus). The males of N. minutus and N. dimorphicus differ in the number of dorsal integumental windows on the cephalothorax (without any in N. minutus, with one integumental window in N. dimorphicus), number of outer spines on P2–P3 exp-3 (three in N. minutus, four in N. dimorphicus), shape of the inner seta on P3 enp-2 (naked in N. minutus, pinnate in N. dimorphicus), and shape of the outer medial and outermost setae on the P5 endopod (pinnate in N. minutus, naked in N. dimorphicus). Nannopus serratus sp. nov. and N. unisegmentatus Shen & Tai, 1964 share the presence of two setae on P2 enp-2 but differ in ornamentation and position of the setae on the mandibular palp, shape of the inner seta on P3 enp-2, and shape of distal seta on P4 enp-2. Nannopus parvus sp. nov. and N. bulbiseta sp. nov. belong to the group of species with the female P5 exopod fused, but these two species can be separated from the others by the presence of two bulbiform pinnate setae on the second segment of the antennule, as well as by the relative length and shape of the inner subdistal pectinate seta of P4 exp-3 (pectinate and 0.5 to 0.7 times as long as those in other congeners), and the shape of outer medial and outermost setae on the P5 endopod (naked only in female). However, they both display unique characters among all congeners. The caudal ramus of N. parvus is trapezoidal or square-shaped, and 0.4 to 0.5 times as long as those in other congeners, and the caudal seta V is very short and spine-like. Nannopus bulbiseta has four and five setae on P2 and P4 exp-3 respectively, the caudal ramus is sub-cylindrical or sub-rectangular, and the proximal part of the female caudal seta V is bulbous and very slender distally. A key to 14 valid species of Nannopus is provided.